The Relationship of Needs during Pandemic with Nurse Coping Strategies in the Covid-19 Emergency Period in Riau Islands, Indonesia - Muthia Deliana; Rian Yuliayana; Elsa Gusrianti (Alliance oh Health Activists (AloHA), 2024)
Indonesia experienced an emergency period of the Covid-19 pandemic in 2020. Nurses, as one of the medical personnel, are at the forefront of handling Covid-19. The high incidence and death rate of Covid-19 has changed the work situation and income of every medical worker, especially nurses. Many nurses worry about meeting unmet needs during the pandemic, such as the need for personal protective equipment, changing income needs, and the need to get support from family and the workplace. This study aimed to determine the relationship between needs during the pandemic and nurse coping strategies during the Covid-19 emergency in the Riau Islands, Indonesia. The design of this study was a cross-sectional test on 224 respondents with accidental sampling. Data analysis using chi-square. This study found a relationship between needs during the pandemic and nurse coping strategies during the Covid-19 emergency period in the Riau Islands, Indonesia. Keywords: needs; nurses; coping strategies